The Metamorphosis - Kafka, Franz (Bantam Classic, London, 1972)
"When gregor Samsa woke up one morning from unsettling dreams, he found hinself changed in his bed into amonstrous vermin.""
Keywords: SAMSA, GREGOR (FICTITIOUS CHARACTER) -- FICTION